A never-ending story: updated 3D cyber-taxonomic revision of the ant genus Zasphinctus Wheeler (Hymenoptera, Formicidae, Dorylinae) for the Afrotropical region - Francisco Hita Garcia; Kiko Gómez; Roberto A. Keller; Bernhard Schurian; Evan P. Economo (ZooKeys)
The ant genus Zasphinctus are fascinating ants due to their distinctive morphology, ecology, and rarity. In this study, a comprehensive revision of Zasphinctus in the Afrotropical region is presented, through a combination of morphological examination under the light microscope and three-dimensional (3D) cyber-taxonomy based on microtomography (micro-CT). Micro-CT based 3D surface models of all species were used for virtual morphological visualisation and examination. The 3D models were virtually visualised, rotated, scaled, and dissected in order to obtain the best shape data for whole specimens or individual body parts. This approach offered a greatly improved character evaluation, allowing the development of an updated taxonomic species delimitation system for the genus. Our revision recognises eight worker-based species, of which three were previously known and five are newly described in this study. Furthermore, based on distinctive morphological differences, two species groups are also proposed. The Z. obamai group includes the species Z. obamai Hita Garcia, 2017 (Kenya), Z. lumumbai Hita Garcia & Gómez, sp. nov. (Democratic Republic of Congo), and Z. wilsoni Hita Garcia, 2017 (Mozambique) while the Z. sarowiwai group contains Z. aprilia Hita Garcia & Gómez, sp. nov. (Democratic Republic of Congo, Uganda), Z. kouakoui Hita Garcia & Gómez, sp. nov. (Ivory Coast), Z. lolae Hita Garcia & Gómez sp. nov. (Ghana), Z. ndouri Hita Garcia & Gómez, sp. nov. (Senegal), and Z. sarowiwai Hita Garcia, 2017 (Cameroon). All species are easily distinguishable through a comprehensive character matrix illustrated by numerous diagnostic illustrations, as well as a traditional dichotomous identification key.